Spider to the fly : a novel - Markert, James, 1974- (Crooked Lane, 2025)
A true crime author helps in a desperate hunt for a killer in this dark and twisted thriller from the deviously inventive horror author that Peter Farris calls the "clear heir to Stephen King." Ellie Isles first became obsessed with the I-64 murders when she saw her own face on one of the victims. Identical to every detail, the woman wasn't her, but she could have been. Compelled to discover the story of her dopplegänger's death, Ellie wrote a bestselling true crime book about the serial killer, dubbed "the Spider." Four years later, the Spider still hasn't been caught, and his victim count is climbing. Many of the bodies remain unidentified, but with Ellie's online network of true crime followers, that's slowly changing. Together they've pooled information to create a massive database that tracks people at risk of becoming Jane and John Does-the homeless, the drug addicted, and the downtrodden-with the hopes that if they become victims, they might at least be identified. Now that Ellie has successfully identified multiple victims, the law enforcement task force tracking down the Spider pulls her in to help-and after Ellie's therapist is arrested for the murders, she is more determined than ever to help catch the Spider. With striking prose and a horror flair, Spider to the Fly is an engrossing serial killer thriller, perfect for fans of The Whisper Man.